Некоторые aспекты внешне-политической деятельности Республики Кaзaхстaн нa современном этaпе - Сарыбаев, М.; Ахметжанова, А. (International relations and international law Journal, 2018)
The article deals with questions of foreign policy activity of Kazakhstan at the present stage. Kazakhstan’s foreign policy are reflected in the «New Kazakhstan’s foreign policy concept of «2014-2020»Approved in 2014, the document was not for the people, for the international community than the unprecedented new as president, the competent authorities have already opened many times in their speeches those tenets and principles on which moves the Republic of Kazakhstan in the international arena. An important priority of Kazakhstan’s diplomacy is, and will be the promotion of Kazakhstan’s foreign policy initiatives abroad, and the presentation of the global community of Kazakhstan’s economic development model of «Kazakhstan-2050». On the basis of the study documents, authors were analyzed and taken further forecast the further direction of foreign policy vector of Kazakhstan. Key words: Republic of Kazakhstan, foreign policy, Kazakhstan’s foreign policy concept.